Financial security of Arab countries: analysis of some aspects - S. Yu. Babenkova (Путеводитель предпринимателя)
Issues of ensuring the financial security of the country have always played an important role not only in times of crises but also in conditions of relatively stable functioning of the economy and financial system. Financial security, along with food and energy security, is part of national economic security and plays a leading role at the macro and micro economic levels. It is especially necessary to note the rapid development of digitalization processes which directly affect the stability of the financial system and its security. The financial systems of Arab countries, being included in the global financial system, are directly or indirectly exposed to almost all possible risks that arise and evolve in the global financial markets and in the global economy. Ensuring financial security in the countries of the Middle East and North Africa region is one of the top priorities for the leadership of these countries. These tasks boil down to, among other things, reducing sovereign risk ensuring unity in regulatory approaches to ensuring cross–border transactions, transparency in trade finance transactions taking into account the imposition of sanctions against some countries, and ensuring cybersecurity in the context of digitalization of financial processes remains an important aspect. This article examined and analyzed some of the aspects of the financial security of Arab countries including taking into account the inclusion of innovative processes in world practice, and there are also presented the problems of the countries of the Middle East and North Africa region which contribute to an increase in the likelihood of imbalance in processes to ensure the financial security of the region generally.